Mayer-Rokitansky-Kuster-Hauser syndrome in a young female: diagnosis and treatment: a case report - Tariq, Asfia; Shamsi, Nida Ilyas (Journal of the Pakistan Medical Association, 2023)
Mayer-Rokitansky-Kuster-Hauser Syndrome is a rare condition in which Müllerian system does not develop and ends up with rudimentary upper vagina and the uterus. As compared to normal physiology of the ovaries and puberty, the patients present with primary amenorrhoea a key clinical symptom. However, the exact aetiology of the disease is still unknown. A few reports considered environmental and epigenetic changes, hormonal imbalance, and cellular receptor abnormalities as possible risk factors associated with the disease. This case was reported at the Department of Family Medicine, The Indus Hospital, Karachi. A 24-year-old woman, married for eight months, presented with primary amenorrhoea and painful intercourse. Upon detailed clinical evaluation and relevant radiological and diagnostic investigation, an assessment, of Mayer-Rokitansky syndrome was made. Keywords: Primary Amenorrhoea, Mullerian agenesis, Mayer-Rokitansky-Kuster- Hauser Syndrome.